PELATIHAN MEMBUAT BAKSO TAHU KRISPI PADA IBU-IBU DI RT 01 RW 03 PERUMAHAN GRAHA BANGUN PERMAI, TARAI BANGUN, KAMPAR, RIAU - Herispon, Herispon; Dehotman, Khornelis; Hendra, Teguh; Herman, Herman; Putra, Eka; Rahmat, Yogi (Jurnal Pengabdian Kompetitif, 2025)
The purpose of holding this Community Service (PKM) is to see the potential of housewives, especially in RT 01 RW 03 Graha Bangun Permai Housing, Tarai Bangun in supporting their family's economy, by carrying out activities that have economic value. Driven by the increasing needs of families from year to year, a solution must be found immediately, when the monthly income is not sufficient from the head of the family or husband, that is when the role of the housewife comes into play to help the family economy. This service method is carried out in the form of short training and simulations/demonstrations of the product objects that are made. The implementation of this PKM activity went according to expectations, and training in making crispy tofu meatballs could be carried out for the mothers who were the audience in this activity. After the PKM was held by lecturers from STIE Riau with the topic and product of making crispy tofu meatballs in RT 01 of the Graha Bangun Permai housing complex, inspiration was opened for a business that could help the family economy